Prior COVID-19 infection is associated with increased coronary artery ectasia and higher thrombus burden in acute coronary syndromes. (3rd May 2023) - To-Dang, B; Zuckerman, M; Cannata, S; Roy, R; Dalton, R; Cannata, A; Webb, I; Melikian, N; Byrne, J; Maccarthy, P; Shah, A; Dworakowski, R; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): This work was part funded by King's College Hospital R&D Grant and was supported by the Department of Health via a National Institute for Health Research Biomedical Research Centre award to Guy's & St Thomas' NHS Foundation Trust in partnership with King's College London and King's College Hospital NHS Foundation Trust. AMS is supported by the British Heart Foundation. Background/Introduction: The COVID-19 pandemic is associated with a profound inflammatory response and a hypercoagulable state in the acute infection, however little is known on whether endothelial dysfunction and hypercoaguability can persist beyond this phase, as well as its impact on acute coronary syndrome (ACS). Purpose: The objective of this study was to investigate the effects of COVID-19 infection on the presentations and outcomes of coronary artery disease in patients with acute coronary syndrome. Methods: Blood samples were obtained from all consenting patients aged 18 or over presenting between 10/06/2020 and 06/05/2021 with suspected ACS. Participants were excluded if they had active COVID-19 infection or if they did not undergo coronary angiography on admission. The blood samples were tested for COVID-19 nucleocapsid antibody and anti-SARS-CoV-2 spike protein receptor binding domain (RBD) antibody levels to determine whether the participants had prior COVID-19 infection, COVID-19 vaccination, or neither at the time of their presentation. Baseline demographics, clinical presentation and coronary angiographic findings were recorded. The patients were followed up at 30 days and 1 year. The primary endpoint was all-cause mortality. The pre-specified secondary endpoints were stroke, repeat MI, unplanned revascularisation or death at 1-year, coronary artery ectasia (defined as dilatation of an arterial segment at least 1.5 times that of the adjacent normal coronary artery), presence of thrombus, and thrombectomy requirement. Results: Of the 280 patients who consented for the study, 5 patients dropped out, 8 were lost to follow-up, 2 did not undergo coronary angiography, and 98 had uninterpretable blood samples for antibody analysis. In the final analysis of the study population of 167 patients (median age 64), 22 (13.1%) had prior infection, 76 (45.5%) were negative for COVID-19 antibodies and 69 (41.3%) were vaccinated. There were no differences in rates of STEMI between the different study groups. There was no difference in the primary endpoint between the groups. However, patients with prior COVID-19 infection were more likely to have coronary ectasia compared to vaccinated and antibody negative patients (57.71% vs 27.5% and 30.3%, respectively p = 0.034). They were also more likely to have thrombus present on angiography (61.9% vs 33.3% and 52.6%, p = 0.019) and more likely to require thrombectomy (19.0% vs 4.3% and 3.9%, p=0.027). Patients with prior COVID-19 infection were also more likely to present with myocarditis (18.2% vs 1.4% and 1.3%, p<0.001). Conclusion: In summary, our findings support the notion that COVID-19 infection leads to persistent endothelial dysfunction and hypercoagulability which portends increased severity of coronary artery ectasia and coronary thrombosis even after recovery from the initial infection. Table of demographics and outcomes Graph of outcomes